April Fool's Day - Fred, Walton; Foreman, Deborah, 1962-; Deborah Goodrich; Lloyd Berry; Mike Nomad; Pat Barlow; Tom Heaton; Jay Baker (USA Hometown Films, 1986)
A group of eight college friends gather together at an island mansion belonging to heiress Muffy St. John to celebrate their final year of school. They soon discover that each has a hidden secret from their past which is revealed, and soon after, they turn up dead. Yet, are they really dead? Or is it just part of some very real and cruel April Fool's jokes? The hostess, Muffy, is the only one who apparently knows what's going on. But then again, is it really her doing the killing?
Nine teenagers in a deserted mansion are being killed off one by one by an unseen killer. Is is real, or just a big practical joke?
Danilo Bach
Language(s): English
Subtitle(s): English, Turkish, Spanish
Keywords: Mystery; Horror